RNA-seq reveals a novel porcine lncRNA MPHOSPH9-OT1 induces CXCL8/IL-8 expression in ETEC infected IPEC-J2 cells - Jiang, Bingyu; Liu, Mingchao; Li, Pei; Zhu, Yue; Liu, Yingying; Zhu, Kaiqing; Zuo, Yuzhu; Li, Yan (Frontiers in Cellular and Infection Microbiology, 2022)
Enterotoxigenic Escherichia coli (ETEC) is a major cause of bacterial diarrhea in piglets, leading to economic losses in the pig industry. In past decades, long non-coding RNAs (lncRNAs) have shown to be widely involved in the regulation of host immunity in porcine infection diseases. In this study, we explored the lncRNAs associated with ETEC F41 infection in IPEC-J2 cells by high-throughput sequencing and bioinformatic analysis. A total of 10150 novel porcine lncRNAs were identified. There were 161 differentially expressed (DE) lncRNAs associated with ETEC F41 infection, of which 65 DE lncRNAs were up-regulated and 96 DE lncRNAs were down-regulated. Functional and KEGG enrichment analysis of predicted target genes of DE lncRNAs indicated they are enriched in cell growth and inflammation-related pathways, such as endocytosis, focal adhesion, TGF-β signaling pathway, and adhesion junctions. We revealed a novel candidate lncRNA MPHOSPH9-OT1 that was up-regulated after ETEC infection. The qRT-PCR validation and ELISA assessment showed the knockdown and overexpression of MPHOSPH9-OT1 resulted in significantly down- and up-regulation of cellular mRNA levels and secreted cytokine level of CXCL8/IL-8, respectively. Meanwhile, MPHOSPH9-OT1 equilibrium is important to maintain the transepithelial electric resistance value and tight junction protein expression of IPEC-J2 cells. This study provides insights into the functionality of novel porcine lncRNAs in host immune responses to ETEC infection.